Reduction of un-burnt in bottom ash of coal fired boilers - Vignesh, E; Chandhru, A; Mahfooz, G; B.Sumanth, K; Gowtham Krishna, R (International Journal of Engineering and Technology, 2018)
In a recent updating world moves related to automation and its improvements but only thread to pause to its electricity. Because it could not be automated and its need to be generated by using different way of methods. In that the Electricity is one the greatest demands that keeps increasing day by day. To feed its supply the necessity of improved power generation techniques is in need. Combustion of coal is one of the traditional methods of producing electricity in developing countries like India. So, it is necessary to have a good optimized boiler to generate power in thermal power plants. The coal fed in should be completely utilized for combustion as the coal is imported at a high rate. But the amount of un-burnt carbon found in the bottom ash slips down the efficiency of a boiler. Here we are going to analyses the causes for more number of un-burnt in bottom ash and methodology to reduce it thereby the efficiency of the boiler gets increased.